2016
DOI: 10.3109/13880209.2016.1173067
|View full text |Cite
|
Sign up to set email alerts
|

Reynosin and santamarine: two sesquiterpene lactones fromAmbrosia confertiflorawith bactericidal activity against clinical strains ofMycobacterium tuberculosis

Abstract: Materials and methods:The dichloromethanic extract of aerial parts of A. confertiflora was separated using chromatography columns. Mycobactericidal activity of the isolated compounds was evaluated using the Alamar Blue bioassay (128-16 lg/mL, 7 days). Cytotoxicity was tested against normal cell line L929 using the MTT ([3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium]) assay (100-3.125 lg/mL, 48 h). , 104-2010, 63-2009, 366-2009 and 430-2010 Mtb strains, respectively. Santamarine had MBCs of 128 lg/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…STM is a sesquiterpene lactone compound present in various plant species such as Inula helenium , Inula japonica [ 12 ], Magnolia grandiflora L. [ 13 ], Ambrosia confertiflora [ 14 ], and Saussurea lappa [ 15 ]. It has been reported to exhibit mycobactericidal effects [ 14 ]. It has also been shown to inhibit the growth of human gynecologic cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…STM is a sesquiterpene lactone compound present in various plant species such as Inula helenium , Inula japonica [ 12 ], Magnolia grandiflora L. [ 13 ], Ambrosia confertiflora [ 14 ], and Saussurea lappa [ 15 ]. It has been reported to exhibit mycobactericidal effects [ 14 ]. It has also been shown to inhibit the growth of human gynecologic cancer cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of STM on Mtb were investigated in six clinical strains. Available data showed that STM had minimal bactericidal concentration (MBCs) of 128 µg/ml against H3Rv and 104‐2010 Mtb strains and minimal inhibitory concentration (MICs) of 128µg/ml against H37Rv, 366‐2009, and 104‐2010 Mtb strains (Coronado‐Aceves et al, ) (Figure and Table ).…”
Section: Antibacterial and Anti‐alcohol Absorptionmentioning
confidence: 99%
“…STM could be isolated from the fruits, flowers, and leaves of Laurus nobilis L (Barla, Topçu, Öksüz, Tümen, & Kingston, ; Fang et al, ), flowers of Tanacetum vulgare ssp. Siculum (Rosselli et al, ) , rhizomes of Costus speciosus (Al‐Attas, El‐Shaer, Mohamed, Ibrahim, & Esmat, ), aerial parts of Ambrosia confertiflora (Coronado‐Aceves et al, ), roots of I. helenium (Li et al, ), and roots of Saussurea lappa (Choi et al, ) (Figure ). Various studies reported the effects of STM, including anticancer (Ma, Chong, Li, Cheung, & Tattersall, ; Mehmood, Maryam, Tian, Khan, & Ma, ; Wu, Zhu, Yan, Khan, & Yu, ), anti‐inflammatory (Matsuda et al, ), antibacterial (Sun, Syu, Don, Lu, & Lee, ), and anti‐ethanol activities (Matsuda, Shimoda, Uemura, & Yoshikawa, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reynosin (2) and santamarine (3; Figure 1) have shown strong bactericidal activity against Mycobacterium tuberculosis, with a minimal inhibitory concentration of 64 μg/mL. [2] In addition, reynosin also suppresses ROS production and reduces COX-2 levels via the NF-KB pathway. [3,4] In vivo studies have recently been carried out on this eudesmanolide, with hepatoprotective effects observed in mouse liver upon exposure to thioacetamide in order to generate apoptosis.…”
Section: Introductionmentioning
confidence: 99%